2021
DOI: 10.3390/jcm10040806
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Post-Concussion-Like Symptoms in the General Injury Population and the Association with Health-Related Quality of Life, Health Care Use, and Return to Work

Abstract: Little is known about post-concussion-like symptoms in the general injury population and the association of these symptoms with outcome after injury. This study aimed to assess the prevalence of post-concussion-like symptoms in a general injury population and describe the association between post-concussion syndrome (PCS) and health-related quality of life (HRQL), health care use, and return to work. In this longitudinal study of a cohort of injury patients, data were collected 6 and 12 months after their Emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…The etiology of PPCS is diverse and multifactorial, with prognosis varying between individuals . The treatment of PPCS remains inconclusive, given that symptoms following a concussion (eg, headache, irritability) are nonspecific and can be commonly reported in healthy individuals, as well as in clinical groups with health conditions unrelated to mTBI . To account for the complexity of PPCS presentation, reference standard guidelines for pediatric and adult populations recommend a comprehensive, interdisciplinary approach to treatment …”
Section: Introductionmentioning
confidence: 99%
“…The etiology of PPCS is diverse and multifactorial, with prognosis varying between individuals . The treatment of PPCS remains inconclusive, given that symptoms following a concussion (eg, headache, irritability) are nonspecific and can be commonly reported in healthy individuals, as well as in clinical groups with health conditions unrelated to mTBI . To account for the complexity of PPCS presentation, reference standard guidelines for pediatric and adult populations recommend a comprehensive, interdisciplinary approach to treatment …”
Section: Introductionmentioning
confidence: 99%
“…In addition, as reflected by the distribution of reference values, these symptoms are more prevalent in the general population subsamples with chronic health complaints. Some studies have shown that the occurrence of PCS is less TBI-specific [ 53 , 54 ] and more related to the premorbid health status of the affected individuals than to TBI [ 55 , 56 ]. Furthermore, individuals suffering from chronic health conditions may experience cognitive, emotional, and somatic symptoms comparable to PCS (e.g., chronic pains [ 21 ], depression [ 51 ], stroke and multiple sclerosis [ 57 ], etc.).…”
Section: Discussionmentioning
confidence: 99%
“…[7,8,9]. Diese als postcommotionelles Syndrom (PCS) bezeichnete Symptomatik, insbesondere affektive Veränderungen und Fatigue, findet sich allerdings auch bei verunfallten Patient*innen ohne Hirnschädigung [10] sowie in der gesunden Allgemeinbevölkerung [11].…”
Section: Folgen Eines Leichten Schädel-hirn-traumasunclassified